Copyright Legal Protection for Portrait on Trademark (Analysis on Cassation Decision Number 52k/Pdt.Sus-Hki/2021) - Sendee Theresia Suriadiningrat; Fitra Deni (Badan Strategi Kebijakan Hukum, 2022)
Legal Protection within the scope of Copyright includes the protection of 2 (two) basic rights, Moral Rights and Economic Rights. The goal is that there are restrictions so anyone cannot use other's Copyrights commercially without permission from the Creator or His Heirs. In the case of the use Mrs. Meneer's Portrait in Trademark without written permission of the Heirs, it becomes debate whether the legal protection of the Portrait remains under the Copyright Law, or its Exclusive Rights have been lost because it falls within the scope of the Trademark Law. The research method used is normative juridical, by reviewing related laws and regulations, and conducting literature studies. The approach is carried out with Cassation Verdict No. 52 K / Pdt.Sus-HKI / 2022. The research concludes that the legal protection of Portraits in Trademarks remains based on the Copyright Law which adheres to the principle of Automatic Protection, so that the Exclusive Rights of the Creators remain. However, the Judge in His consideration determined the plaintiff's legal standing was not based on copyright principles. Based on this case, it is necessary to review the Copyright Law related to the principle of Automatic Protection of the Heirs in order to create justice and legal certainty.